A one-pot strategic construction of functionalized nanomaterial ZIF-90-Rhn for stepwise detection and capturing of Ag+ and formaldehyde from an aqueous solution. Issue 8 (10th March 2022) - Du, Xiaoyu; Li, Mengwen; Du, Man; Shen, Ao; Hao, Xiaohui; Yuan, Jiaxin; Ma, Shufeng; Zhao, Yongwei; Hou, Lala; Li, Ziqi; Yang, Yunxu
Abstract : One-pot strategic development of the functionalized nanomaterial ZIF-90-Rhn for the stepwise detection and capturing of Ag + and formaldehyde from an aqueous solution. Abstract : In this work, a new functionalized nanomaterial, ZIF-90-Rhn, was designed, synthesized and characterized. The synthesis was performed by one-pot strategic construction, post-modification and pre-modification synthesis methods. After encapsulating cyanine dye, Cy-N, into ZIF-90-Rhn, a multi-functional complex of ZIF-90-Rhn@Cy-N was successfully obtained and could be used to detect Ag + in dual-signals (fluorescence signal and visual color signal) by forming an intermedial product of ZIF-90-Rhn@Ag + /Cy-N in an aqueous solution. Subsequently, the intermediate product ZIF-90-Rhn@Ag + /Cy-N could detect formaldehyde (FA) via a stepwise redox recognition reaction through dual-signals. A smartphone portable online detection platform for Ag + and FA using Bluetooth for the color changes under visible light was not realized, and the results are consistent with the fluorescence sensing assay results. Moreover, a chitosan non-woven fabric coated with ZIF-90-Rhn@Cy-N on its surface was considered to evaluate its efficient capturing and removing effects on Ag + and FA in a stepwise actual procedure in water.